General public and workers exposure to high-frequency electric fields in Spanish hospitals Exposición de trabajadores y usuarios a campos eléctricos de alta frecuencia en hospitales españoles - Alberto Caldés Casas; Fanny Serapio Fernández; María del Carmen Bueloha; Rodrigo Picos Gayá; Carlos Campillo Artero (Escuela Nacional de Medicina del Trabajo, 2013)
Introduction: Electromagnetic fields (EMF) are commonly used in hospitals to detect and treat certain diseases or ailments, exposing healthcare workers daily to such fields and casting doubts about workers and patients safety. Objectives: To quantify the actual exposure to high-frequency electric fields of workers and public hospitals users in the Balearic Islands (Spain) and the compliance with the references levels established by the International Commission on Non-Ionizing Radiation Protection (ICNIRP). Material and Methods: High-frequency radiation exposure levels were measured in different areas and compared with ICNIRP levels and Spanish regulation, using a broadband field strength meter and a spectrum analyzer. Results: 1,290 measurements were performed obtaining a median electric field of 0.31 V/m (1st quartile: 0.16 V/m; 3rd quartile: 0.67 V/m). Users and workers are exposed to electric fields from 0.19 V/m to 0.25 V/m in all areas, but Rehabilitation and Radiology. In the former, the patients (not under microwave therapy) are exposed to EMF between 1.87 V/m and 25.71 V/m. Discussion and conclusions: Although effective electric field values are lower than the reference levels, measures should be taken to reduce exposure of especially sensitive people (infants, children, pregnant women,...) and ensure regular monitoring of the exposure. Introducción: Los campos electromagnéticos (CEM) se utilizan con frecuencia en los hospitales para detectar y tratar ciertas enfermedades o dolencias, exponiendo diariamente a los trabajadores sanitarios a esos campos y sembrando dudas sobre la seguridad de trabajadores y pacientes. Objetivos: Cuantificar la exposición real de trabajadores y usuarios de los hospitales públicos de las Islas Baleares (España) a campos eléctricos de alta frecuencia y el cumplimiento de los niveles de referencia establecidos por la Comisión Internacional de Protección contra la Radiación No Ionizante (ICNIRP). Material y métodos: Se midieron los niveles de exposición a radiaciones de alta frecuencia y se compararon con los niveles de ICNIRP y normativa española, usando un equipo de banda ancha y un analizador de espectro. Resultados: Se realizaron 1,290 mediciones obteniendo una mediana del campo eléctrico de 0.31 V/m (1er cuartil: 0.16 V/m; 3er cuartil: 0.67 V/m). Usuarios y trabajadores están expuestos a campos eléctricos de 0.19 V/m a 0.25 V/m en todas las áreas, excepto Rehabilitación y Radiología. En la primera, los pacientes (no tratados con microondas) están expuestos a CEM entre 1.87 V/m y 25.71 V/m. Discusión y conclusiones: Aunque los valores eficaces de campo eléctrico están por debajo de los niveles de referencias, se deben tomar medidas para reducir la exposición de personas especialmente sensibles (bebés, niños, gestantes,...) y asegurar un control periódico de la exposición.